CREATIVE APPROACH TO ENGLISH LESSONS - Khakimova Muattar Muhitdinovna, Akhmadjonova Gulhumor Mirzajonovna (American Journals, 2023)
This article provides several tips and suggestions for conducting a lesson and teachers using creative and interactive techniques in English lessons.
Keywords: creativity, problem situations, creation, new, original, knowledge, method, education